Differences in body composition between metabolically healthy and unhealthy midlife women with respect to obesity status - Vorobeľová, Lenka; Falbová, Darina; Siváková, Daniela (Anthropological Review, 2021)
Body composition (BC) characteristics across metabolic health-by-body mass index categories were examined. Metabolic health (MH) was defined by five biomarkers: waist circumference, blood pressure, levels of triglycerides, high density lipoprotein cholesterol, and fasting glucose. Potential differences in BC characteristics between metabolically healthy obese (MH-O) and metabolically unhealthy obese (MUH-O) women, and between MH normal weight (MH-NW) and MUH normal weight (MUH-NW) women were explored in 276 Slovak midlife women (39-65 years). Body composition parameters were measured with bioimpedance analyzer (BIA 101, Akern, S. r. l.). A simple comparison of the BC data between the subgroups showed significant differences in resistance (Rz, ohm) (p=0.035), muscle mass (MM, kg) (p=0.044), and total body water (TBW, kg) (p=0.047) between MH-O and MUH-O women. However, we did not observe any significant differences in BC characteristics between MH-NW and MUHNW. Specific logistic regression models were used to determine differences in BC characteristics between various obesity phenotypes, with controlling for age, menopausal status, smoking status and sport activity. Our results indicated that increasing age and decreasing Rz were statistically significantly associated with an increased likelihood of exhibiting MUH-O (p=0.031 for age; p=0.032 for Rz). Moreover, other logistic models which included age, menopausal status, biochemical variables and life style factors such as covariates, showed that increasing alanine aminotransferase (ALT) and uric acid (UA) were statistically significantly associated with an increased likelihood of exhibiting MUH-O (p=0.023 for ALT, p=0.010 for UA). In conclusion, MUH-O and MH-O cardiometabolic profiles are characterized by differences in the value of resistance and plasma levels of ALT and UA.